How will the semi-natural vegetation of the UK have changed by 2030 given likely changes in nitrogen deposition?. (January 2016) - Stevens, Carly J.; Payne, Richard J.; Kimberley, Adam; Smart, Simon M.
Abstract: Nitrogen deposition is known to have major impacts on contemporary ecosystems but few studies have addressed how these impacts will develop over coming decades. We consider likely changes to British semi-natural vegetation up to the year 2030 both qualitatively, based on knowledge of species responses from experimental and gradient studies, and quantitatively, based on modelling of species relationships in national monitoring data. We used historical N deposition trends and national predictions of changing deposition to calculate cumulative deposition from 1900 to 2030. Data from the Countryside Survey (1978, 1990 and 1998) was used to parameterise models relating cumulative N deposition to Ellenberg N which were then applied to expected future deposition trends. Changes to habitat suitability for key species of grassland, heathland and bog, and broadleaved woodland to 2030 were predicted using the MultiMOVE model. In UK woodlands by 2030 there is likely to be reduced occurrence of lichens, increased grass cover and a shift towards more nitrophilic vascular plant species. In grasslands we expect changing species composition with reduced occurrence of terricolous lichens and, at least in acid grasslands, reduced species richness. In heaths and bogs we project overall reductions in species richness with decreased occurrence of terricolous lichens and some bryophytes, reduced cover of dwarf shrubs and small increases in grasses. Our study clearly suggests that changes in vegetation due to nitrogen deposition are likely to continue through coming decades. Highlights: Changes in vegetation due to N deposition are likely to continue in coming decades. Reduced occurrence of sensitive lichen species is expected. Nitrophilous species are expected to increase in some habitats. Species richness is expected to be reduced in some habitats. Abstract : UK vegetation is likely to change in future decades as a result of atmospheric nitrogen deposition.